Inhibitory Effects of Urginea maritima (L.) Baker, Zhumeria majdae Rech. F. and Wendelbo and Physalis divaricata D. Don Ethanolic Extracts on Mushroom Tyrosinase - Foroogh Namjoyan, Alireza Jahangiri, Mohammad Ebrahim Azemi, Hamideh Mousavi (Tabriz University of Medical Sciences, 2016)
Background: Tyrosinase is a key enzyme in melanin synthesis from tyrosine. To prevent or treat pigmentation disorders, tyrosinase inhibitors have been used increasingly for medicinal and cosmetic products. The aim of this study is to evaluate inhibitory effects of Urginea maritima (L.) Baker, Zhumeria majdae Rech.f. & Wendelbo and Physalis divaricata D.Don on mushroom tyrosinase. Methods: The inhibitory activities of the hydroalcoholic extracts of plants against oxidation of L-DOPA (as a substrate) by mushroom tyrosinase were investigated. The amount of formed DOPAchrome was determined at 475 nm as optical density. Results: The extracts showed anti-tyrosinase activity weaker than positive control (Kojic acid). The inhibitory activity of tested plants: U.maritima, Z.majdae and P.divaricata against mushroom tyrosinase were 38.61, 29.70 and 25.74 % at 1.67 mg/mL, respectively. Conclusion: The most tyrosinase inhibitory activity was seen for U.maritima. However more investigations on human tyrosinase, toxicological and clinical studies are needed to confirm its activity.